Control of the Electronic Ground State on an Electron-Transfer Copper Site by Second Sphere Perturbations - Morgada, Marcos Nicolás (2014)
The CuA center is a dinuclear copper site that serves as an optimized hub for long-range electron transfer in heme–copper terminal oxidases. Its electronic structure can be described in terms of a σu* ground-state wavefunction with an alternative, less populated ground state of πu symmetry, which is thermally accessible. It is now shown that second-sphere mutations in the CuA containing subunit of Thermus thermophilus ba3 oxidase perturb the electronic structure, which leads to a substantial increase in the population of the πu state, as shown by different spectroscopic methods. This perturbation does not affect the redox potential of the metal site, and despite an increase in the reorganization energy, it is not detrimental to the electron-transfer kinetics. The mutations were achieved by replacing the loops that are involved in protein–protein interactions with cytochrome c, suggesting that transient protein binding could also elicit ground-state switching in the oxidase, which enables alternative electron-transfer pathways.